Worldwide sedation strategies for atrial fibrillation ablation: current status and evolution over the last decade. Issue 12 (19th July 2021) - Garcia, Rodrigue; Waldmann, Victor; Vanduynhoven, Philippe; Nesti, Martina; Jansen de Oliveira Figueiredo, Márcio; Narayanan, Kumar; Conte, Giulio; Guerra, Jose M; Boveda, Serge; Duncker, David
Abstract: Catheter ablation for atrial fibrillation (AF) has become one of the most common procedures in the electrophysiology lab with rapidly increasing volumes. Peri-procedural anaesthesia for AF ablation varies between centres, from general anaesthesia to deep or conscious sedation. The aim of this survey was to assess current sedation practices for AF ablation worldwide and its evolution over the last decade. Centres regularly performing AF ablation responded to an online survey. A total of 297 centres participated in the survey. Overall, the median (interquartile range) number of AF ablation procedures increased from 91 (43–200) to 200 (74–350) per year ( P < 0.001) between 2010 and 2019. The proportion of cryoablation also increased from 17.0% to 33.2% ( P < 0.001). In 2019, the most used sedation technique was general anaesthesia (40.5%), followed by conscious sedation (32.0%) and deep sedation (27.5%). Between 2010 and 2019, the proportion of procedures performed under general anaesthesia (+4.4%; P = 0.02) and deep sedation (+4.8%; P < 0.01) increased, whereas the use of conscious sedation decreased (−9.2%; P < 0.001). The most commonly used hypnotic drugs were propofol and midazolam, whereas the most commonly used opioid drugs were remifentanyl and fentanyl. This worldwide survey shows that the number of AF ablation procedures has more than doubled over the last decade and general anaesthesia remains most commonly used. Studies comparing outcomes between different sedation strategies are needed to guide optimal decision-making.